2021
DOI: 10.1016/j.ajo.2020.09.035
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Incident Causes, and Risk Factors of Visual Impairment and Blindness in a Rural Population in India: 15-Year Follow-up of the Andhra Pradesh Eye Disease Study

Abstract: Purpose: To report 15 year(range:13-17 years) incidence rate of visual loss(blindness and visual impairment (VI)), causes and risk factors for all ages, and for those 40 years or above at baseline for participants in Andhra Pradesh Eye Disease Study(APEDS). Design: Population based cohort studyMethods: All rural participants were interviewed and underwent a comprehensive eye examination. Presenting visual acuity(PVA) was measured using a standard logarithm of minimum angle of resolution chart at 3 meters. Unai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Medical AI models are developed mainly for clinical application to fulfill unmet clinical needs, especially in rural areas. Recently, a few studies have investigated the incidence and prevalence of vision loss in rural areas, such as the Yangxi Eye Study and the Handan Eye Study in China and the Andhra Pradesh Eye Disease Study in India . They found that patients in rural areas have great health care demands but experience the consequences of a lack of health awareness and poor access to high-quality and affordable eye services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Medical AI models are developed mainly for clinical application to fulfill unmet clinical needs, especially in rural areas. Recently, a few studies have investigated the incidence and prevalence of vision loss in rural areas, such as the Yangxi Eye Study and the Handan Eye Study in China and the Andhra Pradesh Eye Disease Study in India . They found that patients in rural areas have great health care demands but experience the consequences of a lack of health awareness and poor access to high-quality and affordable eye services.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a few studies have investigated the incidence and prevalence of vision loss in rural areas, such as the Yangxi Eye Study 18 and the Handan Eye Study 21 in China and the Andhra Pradesh Eye Disease Study in India. 22 They found that patients in rural areas have great health care demands but experience the consequences of a lack of health awareness and poor access to high-quality and affordable eye services. Some previous studies have been conducted to screen for retinal diseases in hospitals and specific disease cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…This group has reported longitudinal visual impairment data over the course of 15 years in the rural population. [ 25 ] In the APEDS III, 69% of the original rural cohort was re-examined. In APEDS III, the crude incidence rate of any visual loss based on PVA and BCVA (best-corrected visual acuity) was 14.6 (95% CI: 13.6–15.7) and 6.3 (95% CI: 6.1–6.4) per 100 person-years, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A certain reluctance of optometry graduates to engage in community-related activities has also been observed, despite the most recent evidence that uncorrected refractive errors and cataract remain the leading cause of avoidable vision impairment in India. 12 This reluctance should thus be actively overcome by creating a clear career path for optometrists in public eye health services and making the activity financially and emotionally enticing for the graduates.…”
Section: The Future: Challenges Opportunities and Solutionsmentioning
confidence: 99%